2021
DOI: 10.1002/admt.202100120
|View full text |Cite
|
Sign up to set email alerts
|

UV‐Shielding and Clusteroluminogenic Cellulose‐Based Films with Tuneable Wettability and Permeability for Dually Self‐Indicating Food Packaging

Abstract: Food packaging plays a vital role not only in extending the shelf‐life and ensuring the safety and quality of food, but also in reducing the occurrence of food loss and waste. This study reports the generation of biocompatible and tuneable cellulose‐based films, which show strong UV absorbing capacity in both UVA and UVB regions to protect the packaged food from UV degradation. By taking advantage of the process of clusterization‐triggered emission, the films can indicate, by displaying changes in the intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Importantly, the physical properties (including the mechanical strength and water vapour permeability) of the films can be tuned easily by manipulating the film constituents 14 . Such high tunability in the properties of a polymeric film has also been observed in a film generated from a cellulose derivative 15 . The UV-shielding capacity and wettability of the film can be altered simply by changing the molecular weight of the derivative or the concentration of the film-forming solution 15 .…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Importantly, the physical properties (including the mechanical strength and water vapour permeability) of the films can be tuned easily by manipulating the film constituents 14 . Such high tunability in the properties of a polymeric film has also been observed in a film generated from a cellulose derivative 15 . The UV-shielding capacity and wettability of the film can be altered simply by changing the molecular weight of the derivative or the concentration of the film-forming solution 15 .…”
Section: Introductionmentioning
confidence: 60%
“…Such high tunability in the properties of a polymeric film has also been observed in a film generated from a cellulose derivative 15 . The UV-shielding capacity and wettability of the film can be altered simply by changing the molecular weight of the derivative or the concentration of the film-forming solution 15 . This enables the properties of the film to be tuned to meet different needs of the food product to be packaged.…”
Section: Introductionmentioning
confidence: 60%
“…produced by the packaged something and improve the life of them. (Lai et al, 2021) As shown in Fig. 3f, there is no obvious difference between the pure regenerated lm and the nal cellulose-based lm for air permeability after surface modi cation.…”
Section: Characterization Of Cellulose-based Lmsmentioning
confidence: 78%
“…The merging of high-barrier packaging components with vacuum or modified-atmosphere food packaging appears to be another promising methodology [189][190][191]. Even though it is technically difficult to eliminate all oxygen, this process can diminish the amount of oxygen in the package [192].…”
Section: Continued Progress Of Antioxidant-active Food Packagingmentioning
confidence: 99%